(untitled) (Scientific journal of the Fergana State University, 2026)
This article considers an inverse boundary problem for a fourth-order partial differential equation that degenerates on the boundary of the domain, for a rectangular domain. The solution to the inverse problem is found in the form of a Fourier series. The existence and uniqueness of the solution to the considered problem are proved.